The press - Fryhofer, John Jacob (My University, 1896)
Introduction: Undoubtably the most powerful factor in the civilization of the world has been the influence of the Press. The history of those nations that endeavored to shackle the thoughts of men is indeed the story of a slow progress and even a description of retrogression. The liberty of thought has ever been the watchword of progress and civilization. We are after caused to wonder why it was the world progressed so slowly in those ages when the printing press was unknown. Perhaps one reason for this slow march among men was due to the absence of vehicle of thought – the Press.
Citation: Fryhofer, John Jacob. The press. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Civilization; Influence; The press; Liberty; Thought; Theses; Manuscripts (documents)